Implementasi Program 7 Kebiasaan Anak Indonesia Hebat Melalui Kegiatan Pembiasaan Pagi Untuk meningkatkan Karakter Disiplin pada Siswa SD Muhammadiyah 1 Kota Tegal - Oktaviana, Ina (CV. ITTC INDONESIA, 2025)
Education has a fundamental role in shaping the character of students, not just the transfer of knowledge. Strong and positive character is an important foundation for individuals to face life's challenges and contribute constructively to society. One crucial character that needs to be instilled early on is discipline. Discipline is the key to success in various aspects of life, from academic achievement to the formation of a responsible and independent person.. Data collection techniques were carried out through in-depth interviews, participatory observations, and documentation studies, with informants consisting of students in grades IV–VI, teachers, and parents. The results showed that the application of these seven habits contributed positively to fostering student discipline, both in terms of time management, personal responsibility, and academic and social discipline. However, significant challenges have been found from the influence of the digital era, such as excessive use of gadgets and distractions from social media, which have the potential to weaken the effectiveness of discipline character building. Teacher support and active parental involvement are important factors in overcoming these obstacles. This study concludes that the 7 Habits of Great Indonesian Children are a relevant and strategic character-building instrument to answer the challenges of character education in the digital era, especially in building student discipline from an early age.